2004
DOI: 10.1007/s00374-004-0804-9
|View full text |Cite
|
Sign up to set email alerts
|

Manioc peel and charcoal: a potential organic amendment for sustainable soil fertility in the tropics

Abstract: In tropical areas, where crop production is limited by low soil quality, the development of techniques improving soil fertility without damage to the environment is a priority. In French Guiana, we used subsistance farmer plots on poor acidic soils to test the effect of different organic amendments, bitter manioc peel (M), sawdust (Sw) and charcoal (Ch), on soil nutrient content, earthworm abundance and yard-long bean (Vigna unguiculata sesquipedalis) production. The peregrine Pontoscolex corethrurus was the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(61 citation statements)
references
References 28 publications
3
56
0
2
Order By: Relevance
“…Although it seems to favour soils with high pH, Marichal et al (2012) found a positive relationship between mortality and pH in soil sampled in Eastern Brazilian Amazonian soils with high pH values (7.41 and 7.96). Juveniles seem more sensitive to pH than adults; Topoliantz et al (2005) found that treatments increasing pH, such as charcoal addition, promoted juvenile activity (i.e., casting).…”
Section: External Characteristicsmentioning
confidence: 95%
“…Although it seems to favour soils with high pH, Marichal et al (2012) found a positive relationship between mortality and pH in soil sampled in Eastern Brazilian Amazonian soils with high pH values (7.41 and 7.96). Juveniles seem more sensitive to pH than adults; Topoliantz et al (2005) found that treatments increasing pH, such as charcoal addition, promoted juvenile activity (i.e., casting).…”
Section: External Characteristicsmentioning
confidence: 95%
“…Apart from these specific studies of boreal and temperate forest soils, charcoal amendment has been associated with general improvement and sustainability of soil fertility in fire-prone native grassland sites in the North American Great Plains (Glaser and Amelung, 2003), and from charcoal amendment of tropical soils (Glaser et al, 2000Topoliantz et al, 2005). While studies thus far support a positive influence of charcoal on boreal forest soils, more extensive studies are required to test its substantive consequences in the field, and especially to disentangle the direct effects of charcoal from those mainly resulting from postfire effects on soil temperature and moisture, and on plant succession.…”
Section: Towards Understanding and Quantifying The Pyc Cycle In Boreamentioning
confidence: 99%
“…Limited studies were available reporting earthworm populations in agricultural systems receiving biochar-like substances or biochar; these studies included [74,75]. Topoliantz et al [74] observed a difference in earthworm abundance for combined charcoal + other organic amendments, compared to a natural fallow field.…”
Section: Historical Impacts and Other Field Studiesmentioning
confidence: 99%